THE ROLE OF THE EXTERNAL AUDITOR IN HARMONIZING THE ENVIRONMENT AND SOCIETY WHEN AUDITING THE IRAQI ECONOMIC ENTITIES A STUDY ACCORDING TO THE INTERNATIONAL AUDITING STANDARD (1010) - Sarah Abdulameer Kamil Abugallal; Hanan Abdulameer Kadhim Al-Musawi; Kareem MuttairHasan (American Journals, 2023)
The research aims to indicate what is the role of the external auditor in the direction of detecting environmental and social damages according to theoretical frameworks, as well as a statement of what is the role of the external auditor in the direction of detecting environmental and social damages resulting from the Iraqi economic entities (industrial and service) as a result of practicing their work in order to limit or prevent those damages that fall on the environment and society, and in the light of the results of the practical side, the external auditor will issue a conservative oversight report on the activities of the Iraqi economic entities (industrial and service) despite their efforts to preserve the environment and protect society from the effects, as well as despite the disclosures about the size of the impact of their activities on the environment and society, but the presence of some damage to the environment and society and one of the most important recommendations is to activate the role of the Iraqi industrial economic entities in addressing the reasons for stopping the factories, which accounted for (31%) of the total factories,Of the total laboratories. In addition to the use of modern methods in the treatment of industrial solid waste hazardous to the environment and society, and the necessity of activating the role of the Iraqi economic service entities in increasing the percentage of the population covered by services as well as moving away from the traditional methods of disposal of the usual waste, which constituted (87.5%) of the total quantities of normal waste.